Age-related changes in Folliculogenesis and potential modifiers to improve fertility outcomes - A narrative review - Ecem Esencan; Gabriela Beroukhim; David B. Seifer (BMC, 2022)
Abstract Reproductive aging is characterized by a decline in oocyte quantity and quality, which is directly associated with a decline in reproductive potential, as well as poorer reproductive success and obstetrical outcomes. As women delay childbearing, understanding the mechanisms of ovarian aging and follicular depletion have become increasingly more relevant. Age-related meiotic errors in oocytes are well established. In addition, it is also important to understand how intraovarian regulators change with aging and how certain treatments can mitigate the impact of aging. Individual studies have demonstrated that reproductive pathways involving antimullerian hormone (AMH), vascular endothelial growth factor (VEGF), neurotropins, insulin-like growth factor 1 (IGF1), and mitochondrial function are pivotal for healthy oocyte and cumulus cell development and are altered with increasing age. We provide a comprehensive review of these individual studies and explain how these factors change in oocytes, cumulus cells, and follicular fluid. We also summarize how modifiers of folliculogenesis, such as vitamin D, coenzyme Q, and dehydroepiandrosterone (DHEA) may be used to potentially overcome age-related changes and enhance fertility outcomes of aged follicles, as evidenced by human and rodent studies.